Utilization of Library Resources Among Undergraduate Business Education Students at Al-Hikmah University, Ilorin, Nigeria - Dauda, Rafat Bukola; Gidado, Sulayman Dauda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This study was carried out to examine the utilization of library resources among undergraduate business education students at Al-Hikmah University, Ilorin. The study had three specific objectives and research questions. The population of the study consisted of all the 91 students who registered for business education programme in the 2023/2024 academic session at Al-Hikmah University, Ilorin. The entire population was considered for the study. The data was collected with the use of a 44-item structured questionnaire which was designed by the researchers. Ninety-one copies of the questionnaire were administered through a research assistant. Only 80 copies of the questionnaire were returned by the respondents and used for the data analysis. The collected data were analysed using mean scores with a benchmark of 2.50 for accepting or rejecting a questionnaire item. The study revealed that there is availability of library resources for the consumption of undergraduate business education students at Al-Hikmah University, Ilorin, the students use them for numerous purposes and the extent of their usage by the students is high. The study concluded that since the university provides the library resources which are needed and the students are utilizing them, it stands the chance of producing competent and qualified business education graduates who can contribute toward repositioning Nigeria to the path of progress. As a way forward, the study among others, suggested that there should be increased budgetary allocation for the library, workshops and orientations should be regularly organized for the students on the use of the library and the students should ensure that they continue to use the library resources for their academic advancement.